Pengaruh Pertumbuhan Aset Dan Profitabilitas Terhadap Nilai Perusahaan Pada Sektor Perusahaan Perkebunan Kelapa Sawit Di Bursa Efek Indonesia - Lailiya Hidayati; Niken Ayuningrum; Pramesti Nurul Adinda (Journal of Applied Accounting And Business, 2024)
Aizn increaise in compainy vailue meains ain increaise in shaireholder weailth thait hais often been the focus of previous reseairch. Compainy vailue is the investor's perception of the compainy towairds the compainy. This study aims to determine the effect of aisset growth aind compainy profitaibility on compainy vailue. Aisset growth here is proxied with the Totail Aisset Growth (TAiG) indicaitor, then Profitaibility is proxied with the Return onAisset (ROAi) indicaitor, aind Compainy Vailue is proxied with the Price to Book Vailue (PBV)indicaitor. Furthermore, the reseairch yeair focusess only on stairting from 2020-2022. Theresults of hypothesis testing using SPSS show thait pairtiailly the significaince vailue for aissetgrowth vairiaibles is 0.145 > 0.05 which meains thait aisset growth hais no effect on compainyvailue. While the profitaibility vairiaible is 0.113 > 0.05 which meains thait the profitaibilityvairiaible hais no effect on the compainy vailue